At the physical limit — chemosensation in sperm. (October 2015) - Strünker, T; Alvarez, L; Kaupp, UB
Highlights: Sperm represent a model for ultra-sensitive chemosensation. Single-molecule sensitivity requires neither cooperative receptors nor on high-gain amplification. During chemotactic navigation, sperm perform stunning mathematical operations. Chemosensation in sperm species is diverse rather than uniform. Photoreceptors and sperm share common signalling motifs. Abstract : Many cells probe their environment for chemical cues. Some cells respond to picomolar concentrations of neuropeptides, hormones, pheromones, or chemoattractants. At such low concentrations, cells encounter only a few molecules. The mechanistic underpinnings of single-molecule sensitivity are not known for any eukaryotic cell. Sea urchin sperm offer a unique model to unveil in quantitative terms the principles underlying chemosensation at the physical limit. Here, we discuss the mechanisms of such exquisite sensitivity and the computational operations performed by sperm during chemotactic steering. Moreover, we highlight commonalities and differences between signalling in sperm and photoreceptors and among sperm from different species.